Theoretical foundations of management of construction enterprises under conditions of deviations - VOVKOVYCH, Yuriy (Ways to Improve Construction Efficiency, 2025)
The theoretical foundations of managing construction enterprises under conditions of deviations form the scientific and methodological basis for ensuring the stability and efficiency of the industry’s operations in situations of uncertainty. Deviations in construction refer to any changes in time, cost, quality, or work scope parameters that occur during project implementation. Their emergence is a natural consequence of the complexity, multifactor nature, and dynamism of the construction environment. Therefore, deviation management is considered not as a reactive function, but as an active component of strategic planning. Modern management theory for construction enterprises is based on the principles of process orientation, adaptability, system integrity, and risk-based thinking. Management under deviation conditions involves continuous monitoring of key performance indicators, analysis of discrepancies between planned and actual values, evaluation of their causes and impacts, and the implementation of corrective mechanisms. Controlling models are applied to integrate financial, temporal, resource, and quality indicators into a unified information system. Among the main management tools are plan–fact analysis, forecasting methods, risk assessment, and process management. A significant role is played by digital management systems (ERP, BIM, PMIS), which enable real-time monitoring and process adjustment. Theoretical approaches rely on the concepts of variance management, risk management, and adaptive management, which allow for minimizing the influence of unforeseen factors and increasing the flexibility of the organizational structure. The key idea is that deviations do not always have a negative character. They can serve as sources of innovation and process improvement if the management system includes mechanisms for their analysis and for using the experience gained in future projects. Consequently, deviation management is viewed as an integrated element of corporate culture, forming an enterprise’s ability for self-organization and sustainable development. Thus, the theoretical foundations of management under deviation conditions combine traditional project management tools with modern approaches in digital analytics, risk management, and behavioral decision-making models. This ensures the development of flexible, adaptive, and resilient construction enterprises capable of operating effectively even in unstable environments.